Human identity and bioethics - DeGrazia, David (Cambridge University Press, 2005)
When philosophers address personal identity, they usually explore numerical identity: what are the criteria for a person's continuing existence? When non-philosophers address it, they often have in mind narrative identity: which characteristics of a particular person are salient to her self-conception? This book develops accounts of both senses of identity.